Capturing the Current-Overpotential Nonlinearity of Lithium-Ion Batteries by Nonlinear Electrochemical Impedance Spectroscopy (NLEIS) in Charge and Discharge Direction - Ernst, Sabine; Heins, Tom Patrick; Schlüter, Nicolas; Schröder, Uwe (Frontiers in Energy Research, 2019)
In this paper, a Nonlinear Electrochemical Impedance Spectroscopy (NLEIS) method is pre-sented that allows capturing the nonlinearity of current and overpotential of a lithium-ion bat-tery individually in charge and discharge direction. A DC bias is applied to the battery to shift its operating point to the nonlinear region of current and overpotential. An alternating current of a low amplitude (AC) is simultaneously superimposed in order to investigate the system additionally in the time domain. NLEIS cell spectra and selected electrode-resolved NLEIS spectra are recorded as a function of state of charge and temperature. Furthermore, Distribu-tion of Relaxation Times (DRT) plots obtained from EIS measurements provide information, which electrochemical processes correlate with the occurrence of nonlinear distortions of cur-rent and overpotential. Moreover, the occurrence of overpotentials and their degree of nonlin-earity at cathode and anode as a function of the state of charge are determined by current pulse measurements.